Matrix Integration with Jitsi Conference Server for Online Learning - Widyastuti, Rini; Suryani, Karmila; Rahmadani, Ade Fitri; Fatrosa, Triadmoko Denny; Syahindra, Wandi (Knowbase : International Journal of Knowledge in Database, 2021)
The current online learning process requires virtual face-to-face media to interact between lecturers and students. However, currently available media requires lecturers to pay a fee to communicate indefinitely. Therefore, we need a media that can facilitate lecturers to do learning easily. This study aims to integrate jitsi with matrix conferences as a real-time online communication medium in learning. This type of research is development research (R&D) with the waterfall method. The steps taken are analysis, design, coding and testing. The analysis is carried out on the system development needs, then the design stage of the Jitsi architecture with a matrix, then coding using PHP and testing through QoS. QoS testing has very good throughput results, poor packet loss, very good delay, and excellent jitter for small-scale applications. It shows that picking video conferencing can be used as a medium of communication in online learning.